Training on Making Natural Disaster Sensor Teaching Aids as an Implementation SDGs in the Merdeka Curriculum for Teachers at Bandarlampung - Abdurrahman, Abdurrahman; Herlina, Kartini; Anggreini, Anggreini (Universitas Lampung, 2025)
Natural disasters are serious threat to life and the environmental ecosystem. Education has an important role in introducing concepts to achieve SDGs in curriculum. However, various challenges faced by physics teachers in Bandarlampung are mainly related to the concept of SDGs and the lack of teaching aids that support learning. Therefore, this activity aims to provide training to physics teachers in Bandarlampung to making and using natural disaster sensor teaching aids. This training uses the IPA (informative-participative-applicative) method including pretest posttests, lectures, discussions, workshops, and presentations. The expected output of this study is an article that will be published in the sinta-4 indexed community service journal, intellectual property rights form of natural disaster sensor teaching aids for the topics of climate change and global warming. The results of the training showed increase teachers' understanding and skills in designing natural disaster sensor teaching aids by utilizing electronic waste. This training become a model for the Development of Continuous Professionalism Improvement of Physics Teachers in the City of Bandar Lampung.